Sediment grain size distribution (cobble-gravel patches) from the Logie Burn, Scotland (2011 to 2014) - Addy, Stephen; Wilkinson, Mark E (In supplement to: Addy, S; Wilkinson, ME (2019): Geomorphic and retention responses following the restoration of a sand-gravel bed stream. Ecological Engineering, 130, 131-146, https://doi.org/10.1016/j.ecoleng.2019.01.013, 2019)
Grain size distribution data from the restored reach (cobble-gravel patches) over 2011 to 2014.
Keywords: morphology; reconnection; River restoration; sand-gravel bed; sediment